PREVALENCE OF LOW BACK PAIN AND LEVEL OF KNOWLEDE ABOUT PATIENT HANDLING AND SHIFTING TECHNIQUES AMONG NURSES OF A PUBLIC SECTOR HOSPITAL IN KARACHI A SURVEY (International Journal of Physiotherapy, 2016)
Background: Low back pain has been found to be the most prevailing musculoskeletal condition as well as a common cause of absence from workplace. Studies report that low back pain is common and accounts for a large number of reported disabilities among nurses. In fact nursing have one of the highest levels of back injury in all occupation groups. The aim of this study is to determine the prevalence of low back pain among nurses in a public sector teaching hospital of Karachi. This study has mainly focused on confounding factors leading to low back pain and level of education among nurses regarding patients handling or shifting techniques.Methods: A self-administered questionnaires comprises of three sections, were used to collect data. The first section requested for socio-demographic information, followed by medical history of back pain during last month and during last year.The second section assessed the medical history of LBP in two categories i.e. during last month and during last year.The third and last section inquired about participants’ level of education about ergonomics with simply in yes or no pattern.The questionnaires were given to 100 nurses. All questionnaires were completed in the presence of theresearcher. Out of 100 questionnaires distributed and recorded, only 47 participants returned the questionnaire.Results: Statistical Package for the Social Sciences (SPSS) version 19.0 was used for statistical analysis. Relationship betweenthe prevalence of low back pain and training in patient moving techniques, manual material handling techniques is significant (p=0.017,p= 0.068). There is a weak relationship with the knowledge of ergonomics, biomechanics and back pain preventive measures (p=0.719,p=0.457,p=0.704).Conclusion: More than two third of the participated nurses were well trained in transfer techniques, manual material training and preventive measures of back pain. But they lack the biomechanical knowledge. The prevalence of back pain is more in the nurses and nursing students in public sector teaching hospitals of Karachi.The relationship between level of education about manual material handling/shifting techniques and frequency of low back pain has been established as well. Key words: back pain, prevalence,patient handling/shifting techniques.